Rekonstruksi hukum islam di era kontemporer: dialektika wahyu, rasionalitas, dan realitas sosial dalam menjawab transformasi zaman - Fanani, Muhammad Fithrah (Maliki Interdisciplinary Journal, 2026)
Islamic law is a legal system with its own unique characteristics, stemming from revelation and evolving through interaction with social, cultural, and historical realities. Since its inception, Islamic law has not existed in isolation, but rather developed within pre-Islamic Arab society, characterized by tribal social structures, economic inequality, and religious practices intermingled with local traditions. This study aims to describe the sociological and anthropological background to the birth of Islamic law and to examine it from an epistemological perspective as the result of the intersection of revelation, reason, and social dynamics. The method used is qualitative research based on literature, with descriptive-analytical analysis of various classical and contemporary literature. The research findings indicate that Islamic law was formed through a continuously evolving dialogical process between divine values ​​and human needs. From a sociological perspective, Islamic law serves to maintain order and build solidarity within Muslim society. Meanwhile, an anthropological perspective indicates that custom or ’urf plays an important role in the formation of law as long as it does not conflict with sharia principles. From an epistemological perspective, Islamic law is understood as a system open to developments through the mechanism of ijtihad and the principles of legal change according to the context of time and place. Thus, Islamic law is not a rigid set of rules, but rather a social ethical framework rooted in divine values ​​while also addressing human needs, thus remaining relevant in facing the challenges of modern society.